Quasi-in-situ observing unusual grain orientation rotation during the process of static recrystallization grain growth in Mg–Zn-Gd alloy - Lingyu Zhao; Zhenhua Wang; Hong Yan; Zhongtang Wang; Quan Liu; Boyu Liu; Zhiwei Shan; Rongshi Chen (Journal of Materials Research and Technology, 2024)
The orientation (including the c axis orientation and crystal direction parallel to rolling direction) evolution of grown recrystallization grains during annealing at 250 °C for 45–180 min in Mg–Zn-Gd alloy was characterized by quasi-in-situ electron backscatter diffraction method. An unusual grain orientation rotation during the process of static recrystallization grain growth, rather than common plastic deformation or recrystallization nucleation process, was observed. Due to the higher storage energy, the growth size in the early stage of annealing (1.41 μm) is larger than that in the late stage of annealing (0.73 μm) for most (∼76%) grains, and corresponding average c-axis rotation angles are 3.65° and 1.39°, respectively, indicating that the larger the increase in grain size, the greater the changing degree in grain orientation. It is speculated that the orientation rotation during grain growth process is mediated by the interaction between dislocations and grain boundaries. The results reported in the current paper can provide a new insight into the study on the relationship between preferential grain growth and non-basal texture formation in rare earth contained Mg alloys.